Beneficial usage of social marketing for small and medium-sized enterprise (SME) in Johor / Hairiani Abdul Hamid ...[et al.] - Abdul Hamid, Hairiani; Kamarolzaman, Noraishah; Omar, Zurina; Wan Abdul Hamid, Wan Nazihah Najwa (UiTM Cawangan Johor, 2019)
The study that was carried out by the researcher is to find out the beneficial usage of social marketing for small-and medium-sized enterprises (SME) in Johor. A total of 100 questionnaires has been distributed to the respondents at Nusajaya Johor. The respondents who were given the questionnaire are picked convenience method in order to get the data. It is a convenience kind of sampling which has been chosen by the researcher. The questionnaires are the primary data regarding Antecedents of social media usage and performance benefits small-and medium-sized enterprises (SME). The independent variables obtain from past research that has been used for this research are interactivity, cost effectiveness and compatibility. The dependent variable which can be obviously seen is the performance benefits using social media for the private company. The data collected is then analyze by the researcher to get the final result that supports and answer the research objective. A few test conducted in order to get the final result which can support the most suitable variable. The researcher found that only Interactivity strategy influencing the performance benefit of using social marketing as it is acceptable, the cost effectiveness is still in a questionable state which still can be accepted and compatibility is unacceptable since it is less than 0.3.